Comparison of the effectiveness of dry needling with dry cupping at upper trapezius muscle in patients with myofascial trigger points. - Shoukat, Imran; Nawaz , Fozia; Shoukat, Khadija; Shoukat, Muhammad Adnan; Shoukat, Muhammad Usman (International Journal of Endorsing Health Science Research, 2021)
Background: Trigger points are palpable nodules or irritable spots present in the skeletal muscles, painful upon pressure. This study is concerned with the pain in the upper Trapezius muscle due to the formation of myofascial trigger points and to make a comparison of the effectiveness of dry needling with dry cupping for treating upper trapezius myofascial trigger points. Methodology: Myofascial trigger points were diagnosed in 30 individuals in the upper trapezius. Subjects were randomized into Group-A (n=15) and Group-B (n=15) using the coin toss method. Patients were evaluated at baseline and after the termination of intervention using the Numeric Pain Rating Scale (NPRS), Neck Disability Index (NDI) and cervical joint range of motions (ROM). Patients from both groups received three sessions of treatment on alternate days in one week. Results: Patients with both interventions resulted in significant improvement of NPRS (p=0.001), NDI (p=0.001), and cervical ranges of motion (p=0.001). However, between groups comparison of outcome measure showed no significant difference in NPRS (p=0.990), NDI (p=0.359), cervical flexion (p=0.457), cervical extension (p=0.382), right cervical lateral flexion (p=0.250), left cervical lateral flexion (p=0.792), right cervical rotation (p=0.336), and left cervical rotation (p=0.242) of motion. Conclusion: The pre-and post-intervention results have concluded that both treatment methods effectively treat myofascial trigger points. There was no significant difference between the two groups for numeric pain rating scale, neck disability index scoring and cervical range of motions.